1997
DOI: 10.1074/jbc.272.15.10080
|View full text |Cite
|
Sign up to set email alerts
|

The Human α-Type Proteasomal Subunit HsC8 Forms a Double Ringlike Structure, but Does Not Assemble into Proteasome-like Particles with the β-Type Subunits HsDelta or HsBPROS26

Abstract: The eukaryotic proteasome is a barrel-shaped protease complex made up of four seven-membered rings of which the outer and inner rings may contain up to seven different ␣-and ␤-type subunits, respectively. The assembly of the eukaryotic proteasome is not well understood. We cloned the cDNA for HsC8, which is one of the seven known human ␣-type subunits, and produced the protein in Escherichia coli. Recombinant HsC8 protein forms a complex of about 540 kDa consisting of double ringlike structures, each ring cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 50 publications
2
81
0
1
Order By: Relevance
“…However, the expression of human a1 or a6 subunits results in the formation of dimers only [15]. It has also been shown that the expression of Trypanosoma brucei a5 subunit results in the formation of a complex of four heptameric rings [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the expression of human a1 or a6 subunits results in the formation of dimers only [15]. It has also been shown that the expression of Trypanosoma brucei a5 subunit results in the formation of a complex of four heptameric rings [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two other a-subunits HsPROs 27 (a1) and HsPROs 30 (a6) can also form protein dimers [15]. In addition, human a7 protein can induce hetero-oligomeric ring formation when coexpressed with a1 and a6 subunits, which are adjacent to a7 in each a-subunit ring of 20S proteasome [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the co-expression of both subunits results in fully assembled proteolytically active proteasomes. Analogously, certain human ␣-type subunits form a double ring-like structure, but the ␤-type subunits are not assembled into a large particle (Gerards et al 1997). The latter observation, however, is puzzling when considering the assembly of native proteasomes, because eukaryotic proteasomes are hetero-heptameric complexes.…”
Section: Structure and Assembly Of 20s Proteasomesmentioning
confidence: 99%
“…Some eucaryal alpha subunits including the human alpha7 (HsC8) and Trypanosoma brucei alpha5 proteins self-assemble into single, double, and even four-stacked protein rings when produced in recombinant E. coli (168,169). The human alpha7 protein also induces heteroligomeric ring formation when synthesized with alpha1 (PROS27) and alpha6 (PROS30) which are adjacent to alpha7 in the final ring of the 20S proteasome (170).…”
Section: Assembly Of 20s Proteasomesmentioning
confidence: 99%